2001
DOI: 10.1021/jp012351l
|View full text |Cite
|
Sign up to set email alerts
|

Computational Studies of the Ground and Excited State Potentials of DMSO and H2SO:  Relevance to Photostereomutation

Abstract: A computational study on ground and excited states of dimethyl sulfoxide (DMSO) and the hypothetical molecule H 2 SO is reported. Full valence CASSCF/6-311+G(3df,2p) with a multireference perturbation theory correction was used for the latter, while DMSO was examined with an active space that neglected only the CH bonds and an analogous basis set that neglected polarization functions on H. A realistic value of 41.5 kcal/mol was obtained for the ground state pyramidal inversion of sulfur for DMSO, though no dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 52 publications
3
23
1
Order By: Relevance
“…It may be noted here that the observed peaks do not match with the reported Rydberg peaks of the CH 3 (CD 3 ) radical [39]. Furthermore, all the features assigned to bands of SO in the present work are well reproduced in the spectra obtained by photodissociation of DMSO-h 6 as well as DMSO-d 6 . This lends weight to our interpretation of these peaks in terms of photoabsorption by the SO radical.…”
Section: High Resolution Studiescontrasting
confidence: 73%
See 2 more Smart Citations
“…It may be noted here that the observed peaks do not match with the reported Rydberg peaks of the CH 3 (CD 3 ) radical [39]. Furthermore, all the features assigned to bands of SO in the present work are well reproduced in the spectra obtained by photodissociation of DMSO-h 6 as well as DMSO-d 6 . This lends weight to our interpretation of these peaks in terms of photoabsorption by the SO radical.…”
Section: High Resolution Studiescontrasting
confidence: 73%
“…Isotopic substitution is a valuable tool for confirmation of vibrational assignments as seen from some of our earlier works [8,9]. In this context, it is of interest to examine the VUV photoabsorption spectrum of the deuterated isotopologue DSMO-d 6 , on which we do not find any VUV photoabsorption study reported earlier. In the present work, photoabsorption spectra of DMSO-h 6 and DMSO-d 6 are studied in the region 35,000-80,000 cm À 1 ( $ 4.3-9.9 eV) using SR.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…CH 3 + SO [11]. The bond dissociation energy for the C-S bond is of the order of 2.3 eV (540 nm) [12] meaning that any of the excited states analyzed here contain enough energy to cleave one of these bonds leading to formation of DMSO products CH 3 SO Å þ CH Å 3 . Amaral and co-workers [11] studied the dissociation of DMSO-d 6 at 210 nm using REMPI-TOFMS (resonance enhanced multi-photon ionisation time of flight mass spectrometry).…”
Section: Introductionmentioning
confidence: 87%
“…For reference, the a 1 D state of SO, which contains a r and a p bond, is bound by 103.2 kcal/ mol. The transition state for inversion is 40.1 kcal/mol higher in energy than the minimum-similar to many other XYSO molecules where X and Y are not bonded together via rings [2,[53][54][55][56][57]. The equilibrium geometry of Cl 2 SO leads to two questions.…”
Section: The CL 2 So Isomermentioning
confidence: 94%